The Definitive Guide to MongoDB: The NoSQL Database for Cloud and Desktop Computing - Plugge, Eelco (Apress, 2011)
MongoDB, a cross-platform NoSQL database, is the fastest-growing new database in the world. MongoDB provides a rich document-oriented structure with dynamic queries that you’ll recognize from RDBMS offerings such as MySQL. In other words, this is a book about a NoSQL database that does not require the SQL crowd to re-learn how the database world works!